Effectiveness of topical vs. combination ciprofloxacin for the treatment of Chronic Suppurative Otitis Media - Nasir Wakeel; Aasma Tariq; Iqra Gull; Hamna Hafeez (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Topical antibiotics are a popular choice for treating chronic suppurative otitis media (CSOM), but there is no consensus on their penetration ability in the middle ear, mastoid cavities, and effectiveness against the causative pathogens. Hence, the present study aimed to compare the efficacy of empirical treatment of Chronic Suppurative Otitis Media (CSOM) with topical ciprofloxacin alone and in combination with oral ciprofloxacin.METHODOLOGY: In this prospective study, 98 consecutive patients presented with diagnosed CSOM of tubotympanic type were recruited from the ENT Department of Bahawal Victoria Hospital. The enrolled patients were randomly subjected to the treatment groups (49 in each group), i.e., topical ciprofloxacin drops alone or oral and topical ciprofloxacin in combination; the therapy continued for 1 week. After 7 days of treatment, patients were assessed to observe the resolution of discharge and adverse effects of the drugs.RESULTS: It was observed that 95.9% of the patients had complete resolution of discharge after 7 days of treatment; the outcomes were comparable in both treatment groups (p=1.00). There was no statistically significant difference between the patients of both treatment groups concerning gender, age, and discharge duration (p>0.05). There were minimal side effects but apparently, they were more frequent among group B patients than in group A.CONCLUSION: It is concluded from the study that topical ciprofloxacin alone is as efficacious as oral and topical combination therapy for the treatment of CSOM.